Ontological Argument for The Existence of God in Farabi's Philosophy - BABATAEV, Abdirashit; GÖKALP, Yusuf (Scientific Journal of Faculty of Theology, 2021)
It is well known that in the history of human thought, the evidence for the existence of God and the criticism of it have been one of the most important issues for many philosophers and theologians. In fact, the existence of God is one of the main problems not only of religious faith, but also of philosophy. Opinions on this subject have been relevant since ancient times. The cosmological, ontological, religious practices, morals, teleological, etc., proposed by theologians and philosophers in connection with the existence of God. The evidence is of interest not only to the intellectual community, but also to the general public. Unlike other evidence, ontological evidence aims to show that God is a necessary being through a proper analysis of the concept of "God." Ontological evidence does not rely on various empirical theories, but seeks to find the concept of the highest order in a rational way. In this article, we analyze the ontological evidence based on the works of the famous philosopher al-Farabi.